The Vanishing Frontier: Towards the Revitalization of Biliran Cultural Heritage - Claire Frances C. Barahan (International Journal Labs, 2023)
This study aimed to explore the cultural heritage of Biliran, an island province of the Philippines, and how it can be revitalized. The methodology used in this study was qualitative and included interviews with local stakeholders, observation of traditional practices, and a review of existing literature. The results indicate that the traditional practices of Biliran are in decline, with the younger generations showing little interest in preserving them. Factors contributing to this decline include the lack of financial resources, the impact of technology, and the absence of a formal education system for preserving traditional practices. The discussion of the results focuses on potential strategies for revitalizing cultural heritage in Biliran, such as increasing access to financial resources, promoting digital literacy among the younger generations, and developing a formal education system to teach traditional practices. The conclusion and recommendation of the study are that a comprehensive strategy should be developed to ensure the preservation of cultural heritage in Biliran. Such a strategy should include initiatives to increase access to resources, promote digital literacy, and develop an education system that is relevant to the local context.